Modification of spider gear back to uniform the stress and improve the anti-wear performance of a real thrust washer. (February 2016) - Wu, Hongxing; Dong, Guozhong; Qin, Liguo; Yuan, Wei; Zhang, Jinyi; Dong, Guangneng
Abstract: The maintenance cost of a heavy truck increases due to the severe damage of thrust washer in the differential. The wear was usually related to the contact stress concentration. In the study, the finite element analysis (FEA) was performed for identifying the source of the abnormal wear of thrust washer. An improved approach of modifying the surface profile of spider gear back was proposed. FEA simulations were further conducted to investigate the effect of different spider gear back parameters on the tribological behavior of thrust washer. The FEA simulation results were verified by tribological experiments. Results showed that: (i) the abnormal wear of thrust washer pairing the original gear was caused by the local stress concentration; (ii) the local stress concentration could be eliminated by modifying the surface profile of spider gear back; (iii) using the modified spider gear back, the wear mass loss of the thrust washer was reduced significantly; (iv) the promising surface radius of spider gear back was 73.15 mm. Highlights: The wear of thrust washer was caused by local stress concentration. The wear location is consistent with the location of Von-Mises stress peak. Modifying the spider gear back surface profile reduces the wear of thrust washer.